Pengaruh Kepemimpinan dan Punishment Terhadap Karyawan Rumah Sakit Rosela Karawang - Ramadhan, Novan Aziz; S, Sungkono (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The research took place in hospitals in Karawang Regency, namely; Rosela Hospital. The research was carried out during the period of February – May 2024. This study uses a descriptive qualitative approach. Informants are selected using the snowball technique, which is the process of determining informants based on previous informants without determining the exact number by digging up information related to the necessary research topics. The results of the study showed that there was a positive and significant influence between leadership style on work discipline, work discipline on employee performance. Directly, leadership style does not affect employee performance, but indirectly affects employee performance. These results show that the better the leadership style, the better the work discipline and employee performance will increase. Improving work discipline in company leadership is able to improve optimal performance.